Prevention of exposure keratopathy in intensive care unit - Shan, Hua (International Journal of Ophthalmology Press, 2010)
AIM: To compare the efficacy for preventing exposure keratopathy of three forms of eye care (artificial tear, moist chamber and polyethylene covers) for intensive care patients. METHODS: Eighty-four patients in Intensive Care Unit (ICU) were randomized to three treatment groups, including artificial tears group, moist chambers group and polyethylene film group. Patients of artificial tear group received two drops of carboxymethylcellulose drops to each eye every 2 hours. The moist chambers and the polyethylene were changed every 12 hours or as needed if they became unclean or torn. The corneal fluorescein stains were performed daily. RESULTS: No of 28 patients (0%) in the polyethylene group and one of the 27 patients (3.70%) in the moist chamber group had exposure keratopathy, compared to 8 of the 29 patients (27.59%) in the artificial tear group. There were statistical significance between the artificial tear group and the moist chamber group (P=0.02), and the artificial tear group and the polyethylene group (P=0.003). The time on eye care every day of the artificial tear group, the moist chamber group and the polyethylene group was 26.69±2.39 minutes, 35.33±2.63 minutes and 7.48±0.87 minutes, respectively. The eye care of the polyethylene group were statistically more time-save than that of the artificial tear group (P<0.001) and the moist chamber group (P<0.001). CONCLUSION: Polyethylene covers are more effective and more time-saving in reducing the incidence of corneal damage in intensive care patients